Resveratrol induces mitochondria-mediated, caspase-independent apoptosis in murine prostate cancer cells - Kumar, Sanjay (Oncotarget, 2017)
Found in the skins of red fruits, including grapes, resveratrol (RES) is a polyphenolic compound with cancer chemopreventive activity. Because of this activity, it has gained interest for scientific investigations. RES inhibits tumor growth and progression by targeting mitochondria-dependent or -independent pathways. However, further investigations are needed to explore the underlying mechanisms. The present study is focused on examining the role of RES-induced, mitochondria-mediated, caspase-independent apoptosis of prostate cancer cells, namely transgenic adenocarcinoma of mouse prostate (TRAMP) cells. These cells were exposed to RES for various times, and cell killing, cell morphology, mitochondrial membrane potential (Δψm), expression of Bax and Bcl2 proteins, the role of caspase-3, and DNA fragmentation were analyzed. TRAMP cells exposed to RES showed decreased cell viability, altered cell morphology, and disrupted Δψm, which led to aberrant expression of Bax and Bcl2 proteins. Furthermore, since the caspase-3 inhibitor, z-VAD-fmk (benzyloxycarbonyl-valine-alanine-aspartic acid-fluoromethyl ketone), had no appreciable impact on RES-induced cell killing, the killing was evidently caspase-independent. In addition, RES treatment of TRAMP-C1, TRAMP-C2, and TRAMP-C3 cells caused an appreciable breakage of genomic DNA into low-molecular-weight fragments. These findings show that, in inhibition of proliferation of TRAMP cells, RES induces mitochondria-mediated, caspase-independent apoptosis. Therefore, RES may be utilized as a therapeutic agent to control the proliferation and growth of cancer cells.